MUDENG Expression Profiling in Cohorts and Brain Tumor Biospecimens to Evaluate Its Role in Cancer - Shin, Juhyun; Choi, Jun-Ha; Jung, Seunghwa; Jeong, Somi; Oh, Jeongheon; Yoon, Do-Young; Rhee, Man Hee; Ahn, Jaehong; Kim, Se-Hyuk; Oh, Jae-Wook (Frontiers in Genetics, 2019)
Mu-2-related death-inducing gene (MUDENG, MuD) has been reported to be involved in the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-associated apoptotic pathway of glioblastoma multiforme (GBM) cells; however, its expression level, interactors, and role in tumors are yet to be discovered. To investigate whether MuD expression correlates with cancer progression, we analyzed The Cancer Genome Atlas (TCGA) database using UALCAN and GEPIA. Differential expression of MuD was detected in six and 10 cancer types, respectively. Validation performed using data from the Gene Expression Omnibus database showed that MuD expression is downregulated in KIRC tumor and correlate with higher chance of survival. Upregulation of MuD expression in GBM tumors was detected through GEPIA and high MuD expression correlated with higher survival in proneural GBM, whereas the opposite was observed in classical GBM subtype. GBM biospecimens anlysis shows that MuD protein level was upregulated in three of six specimens, whereas mRNA level remained relatively unaltered. Therefore, MuD may exert differential effects according to subtypes, and/or be subjected to post-translational regulation in GBM. Correlation analysis between GBM cohort database and experiments using GBM cell lines revealed its positive effect on regulation of protein phosphatase 2 regulatory subunit B'Epsilon (PPP2R5E) and son of sevenless homolog 2 (SOS2). STRING database analysis indicated that the components of adaptor protein complexes putatively interacted with MuD but showed no correlation in terms of survival of patients with different GBM subtypes. In summary, we analyzed the expression of MuD in publicly available cancer patient datasets, GBM cell lines, and biospecimens to demonstrate its potential role as a biomarker for cancer prognosis and identified its candidate interacting molecules.